2013
DOI: 10.1539/joh.12-0264-oa
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Seafood, Serum Liver Enzymes, and Blood Levels of PFOS and PFOA in the Japanese Population

Abstract: PFOA, with medians being highest in the Tokai/Hokuriku/ Kinki region. Conclusions: These findings suggest that the concentrations of PFOS in blood were mainly associated with fish consumption and that the levels of PFOS and PFOA were associated with the serum levels of liver enzymes in Japanese populations. Further investigations are required to clarify the reason for the regional differences in blood levels of PFOS and PFOA in Japan. (J Occup Health 2013; 55: 184−194) Key words: Blood, Fish intake, Perfluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…According to the EFSA (2008) opinion the fish and seafood (50-80%), fruit and fruit products (8-27%) and meat and meat products (5-8%) contributed to PFOS exposure in diet, and in case of PFOA -fruit and fruit products (18-39%) and fish and seafood (7.6-27%). Similar dependencies are reported also by other authors studying the scope of exposure of various populations to these compounds (Berger et al, 2009;Delinsky et al, 2009;Guerranti et al, 2013;Yamaguchi et al, 2013;Vestergren et al, 2008). Similar dependencies are reported also by other authors studying the scope of exposure of various populations to these compounds (Guerranti et al, 2013;Yamaguchi et al, 2013;Vestergren et al, 2008).…”
Section: Introductionsupporting
confidence: 89%
“…According to the EFSA (2008) opinion the fish and seafood (50-80%), fruit and fruit products (8-27%) and meat and meat products (5-8%) contributed to PFOS exposure in diet, and in case of PFOA -fruit and fruit products (18-39%) and fish and seafood (7.6-27%). Similar dependencies are reported also by other authors studying the scope of exposure of various populations to these compounds (Berger et al, 2009;Delinsky et al, 2009;Guerranti et al, 2013;Yamaguchi et al, 2013;Vestergren et al, 2008). Similar dependencies are reported also by other authors studying the scope of exposure of various populations to these compounds (Guerranti et al, 2013;Yamaguchi et al, 2013;Vestergren et al, 2008).…”
Section: Introductionsupporting
confidence: 89%
“…In case of PFOA, the main source of exposure are fruits and processed fruit products (18-39%), and fish and seafood (7.6-27%) (EFSA, 2008). Similar exposure profiles are mentioned also by other authors studying the exposure of various populations to these compounds (Guerranti et al, 2013;Yamaguchi et al, 2013;Vestergren et al, 2008). In contrast to OCs, the magnitude of exposure of humans to PFASs through diet, according the studies of some research centres, is influenced also by the drinking water (Noorlander et al, 2011).…”
Section: Introductionsupporting
confidence: 72%
“…A Swedish report also confirms the existence of a strong correlation between PFAS levels in blood serum and fish consumption (Bjermo et al, 2013). In particular, recent monitoring studies confirmed that fish consumption is an important exposure pathway for PFOS (Berger et al, 2009;Falandysz, Taniyasu, Gulkowska, Yamashita, & SchulteOehlmann, 2006;Haug et al, 2010;Squadrone et al, 2014;Vestergren, Berger, Glynn, & Cousins, 2012;Yamaguchi et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…PFAS exposure in humans primarily originates through ingestion of contaminated food as well as drinking water (Ericson et al, 2008a;Fromme, Tittlemier, V€ olkel, Wilhelm, & Twardella, 2009;Takagi et al, 2008;Vestergren, Cousins, Trudel, Wormuth, & Scheringer, 2008;Vestergren, Berger, Glynn, & Cousins, 2012;Yamaguchi et al, 2013). However, exposure varies depending on the type of PFAS, geographical location, types of food and food consumption patterns (Ullah, 2013).…”
Section: Introductionmentioning
confidence: 99%